Stable isotope and DNA evidence for ritual sequences in Inca child sacrifice - Wilson, Andrew (2007)
Four recently discovered frozen child mummies from two of the highest peaks in the south central Andes now yield tantalizing evidence of the preparatory stages leading to Inca ritual killing as represented by the unique capacocha rite. Our interdisciplinary study examined hair from the mummies to obtain detailed genetic and diachronic isotopic information. This approach has allowed us to reconstruct aspects of individual identity and diet, make inferences concerning social background, and gain insight on the hitherto unknown processes by which victims were selected, elevated in social status, prepared for a high-altitude pilgrimage, and killed. Such direct information amplifies, yet also partly contrasts with, Spanish historical accounts. © 2007 by The National Academy of Sciences of the USA.